Mucopolysaccharidosis Type II: A Kenyan Case Series. (22nd December 2021) - Mungai, L. N. Wainaina; Njeru, C. M.; Nyamai, L. A.; Maina, M.
Abstract : Hunter syndrome, or mucopolysaccharidosis type 2 (MPS2), is a lysosomal storage disorder associated with the involvement of multiple organs such as the central nervous system, hepatomegaly, musculoskeletal, respiratory, cardiac, and hearing. This is due to the accumulation of glycosaminoglycans in body tissues leading to organ failure. Since the laboratories in Kenya do not screen for metabolic diseases, there is the likelihood of assumption that these patients do not exist. These first cases were referred from the eastern part of Kenya where the majority of inhabitants are from the same ethnic community. It was noted that there was increased mortality among boys below the age of 20 years, and hence, the families sought for help in the national referral and teaching hospital. The case series is meant to show that these cases exist and the majority of the patients may be dying before the diagnosis is made. There are no data on MPS2 from Kenya, and the prevalence and incidence are unknown. In this retrospective study, we present a case series of 6 Kenyan boys with MPS2 from a national referral hospital. They were part of 17 patients who had had their blood analyzed for metabolic diseases. All of them were symptomatic with varying degrees of central nervous system involvement. They had undetectable levels of iduronate-2-sulfatase (I2S) enzyme, and three genetic mutations were detected in the IDS gene.